2006
DOI: 10.1111/j.1551-2916.2006.00891.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of Silicon Carbide Pieces by Immersion of Silicon Preforms in Carbonaceous Powders

Abstract: In this work a novel method for production of silicon carbide (SiC) pieces, which involves the heating of silicon (Si) preforms immersed in graphite powder is presented. Such preforms were obtained via low‐pressure injection molding (LPIM), although any other conformation route can be used. The process can be carried out at modest temperatures and gradients in standard furnaces used for processing other ceramics. These features make this process a simpler and cheaper alternative, when compared with other metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…31 At the synthesis temperature of 1150 C, 3C-SiC cannot grow from the reaction between silicon and activated carbon directly. 3 According to the report by Niu et al, 32 33 the action of ZnS is to support more activated Si and SiO 2 . The reactions are shown in the following: 32 33 2ZnS…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…31 At the synthesis temperature of 1150 C, 3C-SiC cannot grow from the reaction between silicon and activated carbon directly. 3 According to the report by Niu et al, 32 33 the action of ZnS is to support more activated Si and SiO 2 . The reactions are shown in the following: 32 33 2ZnS…”
Section: Resultsmentioning
confidence: 91%
“…3 Actually, we have tried to fabricate 3C-SiC free of ZnS powder under the same conditions and found that no 3C-SiC nanospheres could be formed on the Si wafer. This suggests that ZnS powder play a key role in the growth of the 3C-SiC nanospheres.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…1 The chamber has not been vacuumized before being heated, and the Ar gas used in present study is 99% pure. These lead to a trace amount of Copyright: American Scientific Publishers residual oxygen present in the growth chamber.…”
Section: µMmentioning
confidence: 99%